POLITENESS STRATEGIES USED BY TOBA BATAK SELLERS IN SAMOSIR - Yohana Siregar; Rahmah Rahmah (LINGUISTICA, 2014)
ABSTRACT   This study deals with politeness strategies used by toba batak sellers in Samosir. The objectives of this study were (1) to describe the types of  politeness strategies were used by Toba Batak sellers in Samosir, (2) to investigate the type of politeness strategy was mostly used describe the reasons, (3) to describethe roles of politeness to Toba Batak society, and (4) to describe the implication of politeness strategies. The data of this study were the language of conversation between Toba Batak sellers and their buyers. This study applied descriptive quantitative method. The findings show that there are four types of Politeness Strategies used by Toba Batak Sellers in Samosir, namely: Bald on record4 utterances (2.53%), Off record17 utterances (10.75%), Positivepoliteness 129 utterances (81.64%) and Negativepoliteness 8 utterances (5.06%). Positivepoliteness is the most dominant type of Politeness Strategies used by Toba Batak sellers in Samosir. Keyword        :Politeness Strategies, Toba Batak Sellers, Samosir.